Strengthening domestic resource mobilization in Southeast Asia. - Scuratti, Stefano; Asian Development Bank (Manila,Philippines Asian Development Bank, [2021])
Some governments in the region have long struggled to generate enough tax revenue to meet their public expenditure needs. COVID-19 has worsened the situation by reducing government revenues by about 14%. The brief identifies common challenges for tax systems in Southeast Asia and proposes policy actions that will expand the tax base, increase tax compliance, and strengthen tax administration.
Keywords: Taxation reform -- Southeast Asia; Public administration -- Philippines; Finance -- Economic development; Electronic book